Course “The Management Look at Comprehensive Care for Overweight and Obesity Persons in Primary Health Care”: development and application of didactic-pedagogical material for remote teaching (Research, Society and Development, 2022)
This study aims to describe the development and application of the digital teaching material of the course “The Look at Management in Comprehensive Care for Overweight and Obesity Persons”, aimed at managers of Primary Health Care in Ceará. The material was applied remotely in September 2021 and includes 40 class hours. The topics addressed were initially pointed out by the participants themselves as relevant to the management of primary health care, concerning: the context of overweight and obesity; strengthening food and nutrition surveillance; and redirecting of management's view towards the comprehensive care of overweight and obesity. These themes were developed according to lesson plans, with the following structure: reception, presentation of the learning objectives and guiding questions, development of the theme, evaluation and proposal of activities. The synchronous moments were carried out through participatory methodologies, through tools that supported remote teaching, such as: Google Meet, Google Classroom, Padlet and Mentimeter. The process of preparing the material for this course was characterized as a formative action for the team involved and its application was positively evaluated by the managers regarding the themes developed and the didactic-pedagogical conduction.